Study the Effect of Oxygen to Methane Ratio on the Temperature of Partial Oxidation Unit at Direct Reduction Plant by Using CFD - Muhammad Kamal, Jamali (2013)
Direct Reduction Plant is a plant that can produce high quality of iron product. In this plant, the very important thing is the Partial Oxidation (PO) system that allows increasing the productive rate, the quality of Direct Reduced Iron (DRI), and can save the usage of natural gas consumption. Besides, there is a transfer line with two oxygen lances is situated between the gas heater and reactor. The main objective of this study is to consider the oxygen to methane ratio supplied form the oxygen lance on the temperature profile in the combustion chamber. High temperature in the transfer line is needed in order to get high quality of iron product. In order to get the result, the simulation was performed by using Computational Fluid Dynamic (CFD) software that contents Fluent and Gambit. Volume meshing in GAMBIT is very important part before doing simulation in FLUENT as a solver. For further modification, only one lance of oxygen is considered in this study. Besides, the steady state condition of the partial oxidation system also included in this report. From this study, the temperature profile of Partial Oxidation system can be determined thus can give better performance for this system.